Menuju Masyarakat Berketahanan Sosial melalui Pemberdayaan Lembaga Sosial Lokal di Provinsi Kalimantan Tengah - Etty Padmiati (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
Local Social institution empowerment as an effort to enhance and uphold the role and its function to build societal resilience, through giving treatment and means to society that represented by several local institution public figures, which in this context local social institution in Telangah Village, Katingan Ilir Regency, Katingan Regency, Central Kalimantan Province. This research is meant to describe on the implementation of local social institution including its supporting and handicap factor. The reseaarch method used is qualitative descriptive, to know the achievement of the local social institution through giving an action to 30 local public figures and village apparatus. The effectivity of this empowerment program known through a measure comparing between pre and post treatment condition. The result shows that the empowerment targeted society understand on social resilience that indicated through steting an action planning and working program per division or indication, namely social protection for people with social welfare problem division, societal participation on social organization division, conflict control, and local wisdom on natural and social resources management division. The implementation of the working program goes as agreed together. The supporting factor on the implementation of the empowerment is the local government apparatus and the commitment of local public figures. The handicap factor is the limited condition of the local society social resilience forum to collect community fund, to build relation with related institution and corporation, so the outsourcing fund and joint venture have not been implemented. It is recommended that societal resilience forum can be taken as a partner for technical unit and regency social agency to implement social welfare program. So that the forum having an ability to operate the organization and existing program, guiding figures of the forum need an ability establishement by related institutions.